PARTAI POLITIK SEBAGAI BADAN HUKUM DALAM SISTEM KEPARTAIAN DI INDONESIA - Mahmudi, Mohammad (UNIVERSITAS ISLAM MALANG, 2020)
Political parties in Indonesia are growing and growing rapidly, therefore, there needs to be a new idea in the effort to develop and dissolve the bankrupt political party in order to create a system Indonesian parting is a simple multiparty system. The results of this study show that the establishment of a significant political party and efforts to simplify the political party by going through an unusual stage is by means of The application of the bankruptcy political party to the Constitutional Court of its purpose is to efficiencies the country-issued budget for political parties as well as making the system of Indonesia's parting systems a multi-party system that is simple but in terms Do the idea of having to pay attention to several important factors including: democratic, rational, and Non-discriminatory principles.Keywords: Political parties, political party disbandment, simple Multi Party system.